Influence of pandemic waste face mask on rheological, physical and chemical properties of bitumen - Yalcin, Erkut; Ozdemir, Ahmet Munir; Kok, B. Vural; Yilmaz, Mehmet; Yilmaz, Bahadir (Elsevier Sci Ltd, 2022)
Recently, COVID-19 has appeared as an international pandemic, leading to serious risks for humans. Using face masks is one of the most common measures in a wide-ranging prevention program that could control the COVID19 dissemination. Face masks are typically composed of non-biodegradable and non-renewable polymers based on petroleum, which are harmful to nature and lead to health problems. In the present study, disposable face masks, the use of which has increased due to the Covid-19 pandemic throughout the world and which cause environmental pollution, were divided into very small pieces and utilized as a modifier in the bitumen binder. Therefore, this study aimed to provide a solution to such a significant environmental problem. Five different ratios of waste mask and the single ratio of styrene-butadienestyrene (SBS) were added to the pure binder and the rheological, physical, and chemical properties of the modified binders were compared. The result showed that adding a waste mask and SBS to the pure bitumen caused increases in binders' softening point and viscosity and reductions in the penetration value. Waste mask modifications were able to better maintain its elastic properties both at low stress and high-stress levels with increasing temperature. 3% SBS was the binder most affected by temperature rise. As a result, it has been determined that binders containing more than 2% waste mask have better performance characteristics than binders containing 3% SBS in terms of physical and rheological properties.
Keywords: Waste mask; Modification; Environment; Rheology properties; COVID-19